TINGKAT KEPUASAN PENGUNJUNG OBJEK WISATA PUNCAK TETETANA DESA SULUAN KECAMATAN TOMBULU KABUPATEN MINAHASA (The Level of Visitor Satisfaction of Tetetana Peak Tourism Attraction at Suluan Village of Tombulu District, Minahasa Regency) - Jesica Tambuwun; Caroline B. D. Pakasi; Rine Kaunang (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The purpose of this study was to measure the level of satisfaction of visitors in the Tetetana Peak, Suluan Village, Tombulu District, Minahasa Regency. This research was conducted in 3 months, starting from August to October 2019. The data used in this study were primary data,Â obtained directly from selected visitors (respondents) using a questionnaire. The results of this study showed that visitor satisfaction index was 78.72%Â which falled in the satisfied category.Keywords: Level of Satisfaction, Tourist Attraction, Visitor, Tetetana